The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4081/jlimnol.2016.1271
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and sodium as regulators of the recovery of four Daphnia species along a gradient of metal and base cations in metal contaminated lakes in Sudbury, Ontario, Canada

Abstract: Smelting of sulphur-rich metallic ores in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…These metal concentrations were chosen for two reasons. First, they are representative of existing levels of nickel and copper pollution in historically polluted lakes in the Sudbury region, Ontario, Canada where D. pulex is present (Keller and Yan 1991; Celis-Salgado et al 2016). Second, preliminary 14-day toxicity tests indicated that these concentrations have no detectable effects on survival or reproduction in this lineage in the medium used (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…These metal concentrations were chosen for two reasons. First, they are representative of existing levels of nickel and copper pollution in historically polluted lakes in the Sudbury region, Ontario, Canada where D. pulex is present (Keller and Yan 1991; Celis-Salgado et al 2016). Second, preliminary 14-day toxicity tests indicated that these concentrations have no detectable effects on survival or reproduction in this lineage in the medium used (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, fertilization was accompanied by other changes in water chemistry that may have influenced metal toxicity [46]. For example, laboratory analyses show that daphniid metal sensitivity increases when accompanied by low concentrations of calcium [62], an element that has declined in Alexander Lake, Roseland Lake and Black Pond after around 1970 [46]. Although further research is needed to differentiate among these mechanisms, together our findings suggest that complex hierarchical interactions between eutrophication and metal pollution may control daphniid community composition.…”
Section: Discussionmentioning
confidence: 81%
“…6), and on one occasion this theoretical difference has been confirmed in a comparative bioassay. In 2007, Celis- Salgado et al (2016) assessed the toxicity of filtered epilimnetic waters from Middle and Clearwater lakes to a single clone of each of four Daphnia species (D. pulex, pulicaria, mendotae and ambigua) that had been isolated from soft-water lakes in Ontario. Mortality was complete for all four species in the Clearwater Lake assays over 14 days, while Middle Lake waters were less toxic for three of the species, permitting 90, 80 and 40% survival of the D. pulex, D. pulicaria and mendotae clones, respectively.…”
Section: Discussionmentioning
confidence: 99%